Jean-Baptiste Grenouille's Ambition In Patrick Süskind's Perfume: The Story Of A Murderer Novel (1985): A Psychoanalytic Approach - Lestari, Sri (2012)
The study is aimed to show the ambition of Jean-Baptiste Grenouille, the main character in Patric k Süskind's Perfume: The Story of a Murderer. The object of the study of this research is to analyze the novel based on its structural elements and the ambition of Grenouille that deals with id, ego and superego using a psychoanalytic approach. This research is qualitative research. Type of data of the study is text taken from two data sources: primary and secondary. The primary data source is taken from the novel Perfume: The Story of a Murderer written by Patrick Suskind in 1985. While the secondary data sources are other materials taken from literary books, criticism, essays, articles, journal and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The outcome of the study shows the following conclusions. Firstly, based on the structural analysis , it shows that the character and characterization, setting, plot, style and theme of the novel are related into solid unity. Secondly, based on psychoanalytic analysis the novel tells that the major character, Jean-Baptiste Grenouille has psychological problems. The psychological problem of the major character encounters causes the conflict of his mental condition. Then, it develops to become an ambition and influences him to murder 26 virgins. His great ambition to be a master perfumer leads him to be a murderer.